2021
DOI: 10.4271/02-14-03-0020
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Modeling of Pneumatic Braking in Long Combination Vehicles

Abstract: A detailed model for pneumatic S-cam drum brake systems is developed and integrated into a multibody dynamic model for a 33-ft A-double long combination vehicle (LCV). The model, developed in TruckSim ® , is used to study the dynamics of LCVs during straight-line braking at various speeds. It includes the response delay in braking that occurs from the time of application to when the brakes are applied at the drum for all axles. Additionally, the model incorporates an accurate characterization of brake torque v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Yan Daocheng and Li Feiwen used ethnographic field research methods and found that group leaders primarily build interpersonal trust with consumers through emotional labor, which involves emotional interactions both online and offline, thereby creating consumer demand [5]. Zhang Jingmin and Sun Xiaochen believe that platforms should develop incentive measures to increase the efforts of group leaders, as information asymmetry is an important factor affecting the coordination of community group buying supply chains, and incentive mechanisms can mitigate the negative impact of information asymmetry [6].…”
Section: Community Group Buyingmentioning
confidence: 99%
“…Yan Daocheng and Li Feiwen used ethnographic field research methods and found that group leaders primarily build interpersonal trust with consumers through emotional labor, which involves emotional interactions both online and offline, thereby creating consumer demand [5]. Zhang Jingmin and Sun Xiaochen believe that platforms should develop incentive measures to increase the efforts of group leaders, as information asymmetry is an important factor affecting the coordination of community group buying supply chains, and incentive mechanisms can mitigate the negative impact of information asymmetry [6].…”
Section: Community Group Buyingmentioning
confidence: 99%
“…To reasonably simulate the complex braking dynamics, a pneumatic brake subsystem model is developed in Simulink® and integrated into TruckSim®. The details of the brake modeling that includes the brake delays and other effects present in LCVs are described in an earlier paper by the authors [41]. For brevity, the details of the brake model that is integrated into the co-simulation model are not included here.…”
Section: Pneumatic Brake Subsystem Modelmentioning
confidence: 99%
“…Most studies in the control algorithm development domain rely on either kinematic vehicle models or a mixed kinematic, dynamic model, including aerodynamic drag, tire model, powertrain dynamics, etc. [16][17][18][19][20] Even in such fully non-linear models, acquiring all the necessary parameters for intricate longitudinal models, such as gearbox characteristics, remains a challenge due to inherent discontinuities (gear changes). Additionally, due to the real-time computational demands, the application of Model Predictive Control (MPC) using intricate models [21] becomes unfeasible.…”
Section: Introductionmentioning
confidence: 99%